Development of criteria for acceptable previous cargoes for fats and oils: Report of a Joint FAO/WHO technical meeting Bilthoven, Netherlands 7-9 Nov 2006 - FAO, Rome (Italy) (Rome (Italy), 2007)
Sumario (En)
Ilus.; 53 ref.
Keywords: GRASAS; ACEITES; TOXICOLOGIA; RESIDUOS